The Role Of Technology In Era 5.0 In The Development Of Arabic Language In The World Of Education - Masahiko Keshav; Laura Julien; Jessica Miezel (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2022)
Along with the development of the times, the world is currently entering the 5.0 era, which means that all must be prepared for technology in this era, including the Indonesian education system. And this research focuses on the role of technology in era 5.0 on the development of the Arabic language in education. The type of research conducted is library research which is processed qualitatively. The primary data sources in this research are international journals. The secondary data sources in this study were books and national journals related to technology in the 5.0 era and those related to learning Arabic. The results of this study explain how important the role of technology in era 5.0 in learning Arabic is because Arabic is often categorized as a lesson that is considered difficult to understand, and in the learning process, it is often considered boring because of the rigidity of the Arabic learning process with technology that follows developments. The times will make it easier for educators and students and will also attract students' interest in carrying out the learning process, especially in learning Arabic.